It's not all in their heads: the differing role of cognitive factors and non-cognitive traits in undergraduate success. Issue 3 (3rd May 2020) - Caviglia-Harris, Jill; Maier, Karl
ABSTRACT: This paper examines the determinants of retention and GPA for a large population of students enrolled at a U.S. public four-year university. Using a Heckman selection model to correct for sample selection bias, we find that cognitive factors positively relate to GPA over the college career and that non-cognitive factors have a stronger association in earlier semesters. These results suggest that policy to increase retention should focus on building community, whereas policy to improve academic achievement should focus on developing the perseverance required to build study skills in the early college years.